2011
DOI: 10.1186/1752-0509-5-99
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network analysis reveals active microRNAs and their functions in gastric cancer

Abstract: BackgroundMicroRNAs (miRNAs) are a class of endogenous, small and highly conserved noncoding RNAs that control gene expression either by degradation of target mRNAs or by inhibition of protein translation. They play important roles in cancer progression. A single miRNA can provoke a chain reaction and further affect protein interaction network (PIN). Therefore, we developed a novel integrative approach to identify the functional roles and the regulated PIN of oncomirs.ResultsWe integrated the expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 43 publications
1
65
0
7
Order By: Relevance
“…This is mainly a result of patients being diagnosed late and the consequently low surgical resection rate (1)(2)(3). An improved understanding of the pathogenesis and pathological characteristics of gastric cancer will provide a novel method to ensure an early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly a result of patients being diagnosed late and the consequently low surgical resection rate (1)(2)(3). An improved understanding of the pathogenesis and pathological characteristics of gastric cancer will provide a novel method to ensure an early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S1 Distribution of differential expression of miRNAs (log 2 fold changes) dependent on the origin of analyzed samples. Four publicly available datasets, obtained on Agilent platform were used for distribution comparison: GSE13860 and E-MTAB-96 datasets belonging to miRNA cross-platform comparison studies (Table S1); GSE21036 dataset, 28 paired primary prostate tumors and normal matched tissues profiled on Agilent v2.0 arrays, designed on miRBase release 10.1 [12]; GSE28700 dataset, 22 paired gastric cancers and normal matched tissues profiled on Agilent v1.0 arrays, designed on miRBase 10.1 [13]. (PDF) Figure S2 RLE plots.…”
Section: Integration Of Mirna and Mrna Expression Datamentioning
confidence: 99%
“…MiRNA can indirectly influence rifampin-induced drug deposition through gene regulation [11,[13][14][15]. Proteins are synthesized from mRNA templates through a highly conserved process, many studies have reported that the functions of miRNAs can be understood by analyzing miRNAs-regulated mRNA-related PIN [16][17][18].…”
Section: Introductionmentioning
confidence: 99%